TRACER STUDY PADA LULUSAN PRODI PENDIDIKAN FISIKA - Yuli Prihatni; Puji Hariati Winingsih (LP2M Universitas Sarjanawiyata Tamansiswa, 2016)
Tracer Study is important to be done, with the implementation of tracer studies will be obtained feedback can reveal useful information for Physical Education and Study programs can then be used for the improvement and quality assurance for internal and external quality assurance. This study aims to determine 1) Profile Physical education graduate study program, 2) Suitability Education Graduates by type of work, 3) to determine the input graduates for the development of Physics Education Study Program This research is a descriptive study with a quantitative approach. This study took a random sample. Data collection was done by using questionnaires and documentation. Analysis of data using statistical descriptive analysis in the form of tabulation and visualization in the form of pictures and graphics. The results showed that the profile of a graduate program of study Physical Education variegated, amounting to 92% consistently worked as a science teacher at the junior high and high school physics teacher. By 75% the salaries of graduates of Physics Education> 1 million. This means public recognition of the Physical Education graduates is quite high. Conformance level of education obtained by the type of work, the graduates who worked as a teacher of Physics at the equivalent of high school, 85% support the work, for a science teacher for 60% support for the work and other work only 30% support the work. The waiting period physical education graduate study program is as much as 96% get a job <6 months. Put alumni to study Physical Education Program is room for improvement in the field of infrastructure, soft skills, learning and quality of lecturers.Â Keywords: Tracer study, graduates, physics